Catalytic Asymmetric Isomerization of (Homo)Allylic Alcohols: Recent Advances and Challenges. Issue 11 (24th March 2022) - Zhang, Xue‐Xin; Zhang, Ying; Liao, Ling; Gao, Yang; Su, Heng E. M.; Yu, Jin‐Sheng
Abstract: Catalytic asymmetric isomerization of allylic or homoallylic alcohols into synthetically useful carbonyl compounds is a redox‐neutral and 100 % atom‐economic transformation, which is of great interest and has gained increasing attention from both academic and industry. This minireview summarizes the advances in catalytic enantioselective isomerization and it involved tandem reactions over the past five years, also discusses their advantages and limitations, and expounds the synthetic chances still open for further development. Abstract : Asymmetric isomerization : This Minireview discusses recent advances in catalytic asymmetric isomerization of (homo)allylic alcohols and it includes tandem reactions, which would provide the readers with some inspiration to develop new and more useful allylic alcohol isomerizations.